Foreign Direct Investment and Tax Revenue Performance in Nigeria (1987-2016): Terrorism-Effect - Egwakhe, A. J.; Odunsi, K. O. (International Journal of Management Excellence (ISSN: 2292-1648), 2019)
The study argued that terrorism exhibited negative effect on the interaction between foreign direct investment (FDI) and tax revenue performance in Nigeria from 1987-2016. An econometric model was formulated and hierarchical regression analysis conducted. Jarque-Berra test indicated that the series are normally distributed meaning that the data were robust, appropriate and met goodness of fit standard. The results revealed that the interaction between FDI and Tax revenue performance (-75213.95 and probability 0.000) was negatively moderated by Terrorism with the Adjusted R2 0.9098 and F-stat 95.144. Recommendation was anchored on nationwide security improvement to increase tax returns, tax payment, and foreign investors’ confidence on investment in Nigeria.